2005
DOI: 10.1016/j.cub.2005.02.026
|View full text |Cite
|
Sign up to set email alerts
|

The Drosophila Grp/Chk1 DNA Damage Checkpoint Controls Entry into Anaphase

Abstract: It is well established that DNA damage induces checkpoint-mediated interphase arrest in higher eukaryotes, but recent studies demonstrate that DNA damage delays entry into anaphase as well. Damaged DNA in syncytial and gastrulating Drosophila embryos delays the metaphase/anaphase transition . In human cultured cells, DNA damage also induces a delay in mitosis . However, the mechanism by which DNA damage delays the anaphase onset is controversial. Some studies implicate a DNA damage checkpoint , whereas other s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
66
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(69 citation statements)
references
References 31 publications
3
66
0
Order By: Relevance
“…Indeed, the partial decline in myt1 mutant PH3-labeled cells observed immediately after exposure to ionizing radiation could reflect activation of an otherwise dispensable Wee1-regulated premitotic checkpoint mechanism. The remaining PH3-positive cells that persisted long after irradiation in myt1 mutant discs could be arrested in mitosis by an alternative regulatory mechanism that was responsive to DNA damage (Sanchez et al 1999;Royou et al 2005;Kim and Burke 2008;Musaro et al 2008). Further studies will be needed to clarify the respective roles of dMyt1 and dWee1 in cellular responses to DNA damage.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the partial decline in myt1 mutant PH3-labeled cells observed immediately after exposure to ionizing radiation could reflect activation of an otherwise dispensable Wee1-regulated premitotic checkpoint mechanism. The remaining PH3-positive cells that persisted long after irradiation in myt1 mutant discs could be arrested in mitosis by an alternative regulatory mechanism that was responsive to DNA damage (Sanchez et al 1999;Royou et al 2005;Kim and Burke 2008;Musaro et al 2008). Further studies will be needed to clarify the respective roles of dMyt1 and dWee1 in cellular responses to DNA damage.…”
Section: Discussionmentioning
confidence: 99%
“…These early studies, and many others since, have shown that mitotic DNA damage mediates a slowing of phase progression by activating, or delaying the inactivation, of the SAC. Recent research in a number of species has determined that the incorporation of mitotic DNA damage leads to the activation of SAC component BubR1, which is thought to be vital in the mitotic delay (Royou et al, 2005;Fang et al, 2006;Choi and Lee, 2008). It is generally believed that widespread DNA damage or structural changes to chromatin affect the centromere region, which results in the disruption of kinetochore structure/function (Garber and Rine, 2006).…”
Section: Inactive Sacmentioning
confidence: 99%
“…An alternative mitotic DNA damage checkpoint mechanism was devised from studies in Drosophila embryos in which ATM (Mei-41 in the fly) induction is thought to cause a mitotic delay by stabilising Cyclin A, which prevents anaphase onset (Su and Jaklevic, 2001;Laurencon et al, 2003). It has also been shown in Drosophila embryos that DSBs, away from kinetochore regions, retard mitosis progression through activation of a Chk1 signalling pathway (Royou et al, 2005). Works by Huang et al, have demonstrated that DNA damage in human cells elicits a mitotic exit blockade dependent on BRCA1 and Chk1 (Huang et al, 2005).…”
Section: The Potential Existence Of Dna Damage Mitotic Checkpointsmentioning
confidence: 99%
“…DNA damage does not affect entry into M (NA). The role of grp in regulating progress through M in response to damaged DNA in larvae was published recently (Royou et al, 2005) but not shown in the Table. *Data presented in this paper.…”
Section: Western Blottingmentioning
confidence: 99%
“…A recently published report documents the regulation of metaphase-anaphase transition by checkpoints in response to DNA double-strand breaks in Drosophila larvae (Royou et al, 2005). This checkpoint, first described in embryos, is not limited to the embryo.…”
Section: Metaphase-anaphase Checkpointmentioning
confidence: 99%